Sistem Absensi Barcode Berbasis Web dengan Menggunakan Smartphone sebagai Pemindai Barcode di STMIK Indonesia Banda Aceh - Asmuzar Asmuzar; Adi Ahmad (Jurnal Manajemen Sistem Informasi (JMASIF), 2025)
Manual attendance methods are still commonly used in university settings and often lead to several problems, such as delayed record-keeping, data inaccuracies, and time-consuming recap processes. To overcome these issues, a web-based attendance system was developed using barcode scanning via smartphones. The system was designed using the Spiral model, allowing for gradual development and adaptation to user requirements. The design process involved direct observation and interviews with academic staff to understand the existing workflow. The application consists of two main components: a desktop application for data input and management, and an Android application that allows students to scan barcodes as proof of attendance. All scanned data is automatically stored in a local database via a Wi-Fi network. Testing was carried out using the blackbox method to ensure that all features functioned as intended. The results showed that the system increased recording speed, reduced errors, and simplified the generation of attendance reports. A simple user interface also made the system easy to operate without the need for special training. This system offers a practical solution to support a more efficient and organized academic administration process.